2011
DOI: 10.3201/eid1703.100604
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria in Respiratory Tract Infections, Eastern Asia

Abstract: we searched PubMed (www.ncbi.nlm.nih.gov/pubmed) for Englishlanguage articles about nontuberculous mycobacteria in Asia. The search strategy was as follows: "mycobacteria, atypical" [MeSH] AND "Asia" [MeSH] OR "atypical mycobacterium infections" [MeSH] AND "Asia" [MeSH]. We chose the term Asia to incorporate the following countries: Brunei,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
60
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 29 publications
(51 reference statements)
15
60
0
3
Order By: Relevance
“…The high isolation frequency of RGM, particularly M. abscessus, was also noted in previous studies focusing on this region [19][20][21]. The reason for the high isolation rate of RGM in Asian countries remains unclear, although geographical or climatic factors, host and laboratory factors have been suggested [20]. An important reason to perform studies on the geographical distribution of NTM is to help identify factors associated with differences in worldwide isolation patterns of specific species.…”
Section: Discussionmentioning
confidence: 70%
“…The high isolation frequency of RGM, particularly M. abscessus, was also noted in previous studies focusing on this region [19][20][21]. The reason for the high isolation rate of RGM in Asian countries remains unclear, although geographical or climatic factors, host and laboratory factors have been suggested [20]. An important reason to perform studies on the geographical distribution of NTM is to help identify factors associated with differences in worldwide isolation patterns of specific species.…”
Section: Discussionmentioning
confidence: 70%
“…For example, in most of Asia and New Zealand after MAC, RGM have generally been the most frequently identified species but India reports no PNTM due to MAC and attributes 40% to M. fortuitum and 33% to M. kansasii [34]. In Britain, MAC (43%), Mycobacterium malmoense (14%) and M. kansasii (13%) were the most frequently isolated species from respiratory specimens [35].…”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, the clarithromycin MIC values of 33 of 36 M. massiliense isolates were Յ2 g/ml when the broth susceptibility test results were read on day 5; however, 11 (33.3%) of the 33 isolates exhibited clarithromycin MICs of Ͼ16 (Ն32) g/ml during the 14-day observation. Previous studies have shown that rapidly growing mycobacteria, especially those of the M. abscessus complex, are the most common clinical isolates of mycobacteria and are a major cause of pulmonary disease due to nontuberculous mycobacteria (NTM) in Asia (2,3,(18)(19)(20). Saleeb et al reported that MALDI-TOF MS can be incorporated into the work flow of the microbiology laboratory for rapid and accurate identification of most species of mycobacteria (16).…”
mentioning
confidence: 99%